Gravesʼ Orbitopathy: Current Concepts for Medical Treatment - Oeverhaus, Michael; Stöhr, Mareile; Möller, Lars; Führer, Dagmar; Eckstein, Anja (Klinische Monatsblätter für Augenheilkunde, 2021)
Background The therapy of severe manifestations of Gravesʼ orbitopathy (GO) is still a challenge and requires good interdisciplinary cooperation. It is especially important to use stage-adapted anti-inflammatory therapy to avoid irreversible damage.Material and Methods Discussion of the latest results of multicentre randomised therapy studies on anti-inflammatory treatments for Gravesʼ orbitopathy, as well as new therapeutic concepts.Results Mild cases of GO can be treated with only selenium supplementation and a watchful waiting strategy. In the moderate-to-severe active form of GO, primary therapy consists of i. v. steroids (cumulative 4 – 5 g) in combination with orbital irradiation in patients with impaired motility. In patients with insufficient therapeutic response after 6 weeks, treatment should be switched to other immunosuppressive agents. In severe sight-threatening disease, bony orbital decompression is usually necessary. As basic research has improved our understanding of the underlying pathophysiology of GO, it has been possible to develop targeted therapies for GO. Teprotumumab, an IGF-1 receptor antibody, was effective in treating GO patients in a phase III trial and should soon be awarded approval for Europe.Conclusion The current therapy concept for Gravesʼ orbitopathy is as follows: first anti-inflammatory therapy then surgical correction of the permanent defects. This may soon be modified, due to the use of targeted therapies.Hintergrund Die Therapie schwerer Manifestationsformen der endokrinen Orbitopathie (EO) ist immer noch eine Herausforderung und verlangt eine gute interdisziplinäre Zusammenarbeit. Von besonderer Bedeutung ist die stadiengerechte antientzündliche Therapie, um irreversible Schäden zu vermeiden.Material und Methode Diskussion der neuesten Ergebnisse multizentrischer randomisierter Therapiestudien zur antientzündlichen Therapie der endokrinen Orbitopathie und von neuen Therapiekonzepten.Ergebnisse Bei der milden Form der EO kann der Spontanverlauf unter Selensupplementation abgewartet werden. Bei der moderat schweren aktiven Form der EO besteht die Primärtherapie aus einer i. v. Steroidstoßtherapie (kumulativ 4 – 5 g) in Kombination mit einer Orbitaspitzenbestrahlung bei Motilitätsstörungen. Bei ungenügendem Ansprechen nach 6 Wochen kann eine immunsuppressive Therapie hinzugefügt werden. Bei schwerer visusbedrohender Manifestation ist meist eine knöcherne Orbitadekompression die Therapie der Wahl. Durch konsequente Grundlagenforschung konnten inzwischen auch für die EO zielgerichtete Therapien entwickelt werden. Der IGF-1-Rezeptor-Antikörper Teprotumumab zeigte sich in einer Phase-III-Studie als effektiv, sodass in Kürze mit einer Zulassung zu rechnen ist.Schlussfolgerung Das aktuell noch gültige Therapiekonzept bei der endokrinen Orbitopathie der zunächst antientzündlichen Therapie gefolgt von der operativen Korrektur der bleibenden Defekte ändert sich möglicherweise durch den Einsatz zielgerichteter Therapien in der Zukunft.
Keywords: Graves; Graves orbitopathy; treatment; lids; orbit; strabismus